TRANSFORMING CLINICAL CENTERS: ECOSYSTEM MANAGEMENT FOR IMPROVED EFFICIENCY - Pastuch Tokars , Francisco; Alberti Fischer , Isabela; Wernecke Fumagalli , Luis André (Caderno PAIC, 2024)
This study defines and analyzes a medical ecosystem management model for clinical centers, focusing on theory and practical application, aiming to improve service efficiency and patient satisfaction through continuous feedback mechanisms. The growth of the healthcare market, driven by technological advancements, population aging, and increased life expectancy, demands new management strategies that integrate different areas of medical care and the clinic with the environment. The research compares the theoretical model with current processes in a real clinic, highlighting the importance of integrated digital medical records and continuous feedback systems, and identifying the lack of efficient communication among healthcare professionals as a significant barrier. The adoption of this ecosystem management model has the potential to transform the management of clinical centers, increasing operational efficiency, improving service quality, and enhancing patient satisfaction. It suggests that clinics and hospitals integrate advanced technologies and implement effective feedback systems to optimize their processes and strengthen their position in the competitive healthcare market.